A Family History of Dilated Cardiomyopathy Induced by Viral Myocarditis - Thomas Cognet; Olivier Lairez; Pauline Marchal; Jérôme Roncalli; Michel Galinier (Case Reports in Cardiology)
Myocarditis can lead to acute heart failure, cardiogenic shock, or sudden death and later, dilated cardiomyopathy (DCM) with chronic heart failure. We report the cases of two DCM induced by acute and past myocarditis in the same family and expressed by its two main complications within few weeks: an hemodynamic presentation as a fulminant myocarditis rapidly leading to cardiac tranplantation and a rythmologic presentation as an electrical storm leading to catheter ablation of ventricular tachycardia. These cases ask the question of the family predisposition to viral myocarditis leading to DCM.